Review on Ethnobotanical Studies on Traditional Medicinal Plants Used to Treat Livestock and Human Ailments in Tigray Region, Ethiopia Ethnobotanical Review on Traditional Plants with Medicinal Values: Exploring Ethnobotanical Significance of Traditional Medicinal Plants in Aravalli District, India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper provides a conglomerated review that emphasises on ethnobotanical data that are available in and around the Aravalli district, India. These plants are endowed with medicinal value and are being traditionally utilized for treating human ailments in Aravalli.This paper intends to explore on the various plant species with ethnobotanical significance via performing a detailed and well-structured review from the data acquired from the occupants (i.e.) natives, tribal communities and elders who are well-versed with the plant species that are grown in their locality. From the inferred analysis, we assess their inherent nature through as largely the source of plant species were from wild vegetation followed by home garden. Herbs were the frequently used plant species followed by trees. Leaf materials were the most used followed by roots. Crushing was the frequently used method of preparation. Mostly the medicine was administered by oral followed by dermal. Large proportions of the medicinal plants were threatened by agriculture expansion followed by drought. Medicinal plants sold in the market were not primary for medicine rather for other purposed (food, spice, beverages). This knowledge concerning with plant's ethno medicinal value could be witnessed to be transferred to its younger generation for thorough utilization of plants which are naturally endowed with rich secondary metabolites.